The Formation and Essence of the Science of Sufism (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article reveals the dictionary and terminological meanings of the word tasawvus, the stages of its formation as a science, the aspects that motivated the formation of the first mystics and sects, as well as the main ideas and their content in the science of tasawvus.